Humanitarian Rehabilitating A Drugged Society - - (Bridge Publications, 2012)
By this book you may have noticed that society is rapidly going downhill. Inflation, lack of fuel and even wr cast deep shadows over the world. and the most serious part of this is that drugs, both medical and street drugs, have disable a majority of those who could have handleit, including the political leaders, and have even paralyzed the coming generations.